THU0484 Ro60 expression decreases with age in peripheral blood mononuclear cells of children and adolescents and correlates with tlr7 stimulation in pdcs of prepubertal children. (15th June 2017) - Radziszewska, A; Webb, K; Peckham, H; Ioannou, Y
Abstract : Background: Auto-antibodies to the RNA binding protein Ro60 are present in patients with autoimmune disorders such as systemic lupus erythematosus (SLE). In addition to its established role as an auto-antigen, Ro60 has been found to bind Alu RNA retroelements whereby it may target Alu retroelement RNA for degradation suggesting a novel putative function of this auto-antigen. If Ro60 modulates the amount of cellular RNA then one may hypothesise an association with toll-like receptor (TLR) 7 stimulation threshold. Objectives: To measure the physiological levels of intracellular Ro60 protein in healthy children and adolescents and investigate a possible link between Ro60 protein expression and interferon-α (IFN-α) production after TLR7 stimulation. Methods: Peripheral blood mononuclear cells (PBMCs) were isolated from blood from 48 healthy children and adolescents (age range 6.7–17.9 years old). Cell lysates from thawed PBMC samples were tested for Ro60 expression by Western blot. PBMCs were also stimulated for 20 hours with TLR7/8 agonist R848, at 1ug/ml in the presence of brefeldin A, and plasmacytoid dendritic cell (pDC) IFN-α expression was measured using flow cytometry. Statistical tests to measure correlation between IFN-α expression in (pDCs) and PBMC Ro60 expression were performed using SPSS. Results: Ro60 expression in PBMCs correlated negatively with age (Spearman's rho = -0.317, p=0.032). When participants were divided into two groups based on their self-reported puberty status, Ro60 expression was higher in the pre-pubertal group (p=0.02). There was, however, no difference in Ro60 expression between males and females (p=0.44) or when sexes were stratified according to pubertal status. pDC IFN-α production after TLR 7 stimulation, did not correlate with ex vivo PBMC Ro60 expression overall (Spearman's rho =0.159, p=0.302) however a moderate positive correlation was observed in pre-pubertal samples only (Spearman's rho =0.554, p=0.021). Conclusions: Ro60 expression decreases with age in healthy young people. These findings need to be confirmed in a larger cohort and further studies are necessary to investigate the link between Ro60 expression and TLR7 signalling across different age groups as well as in patients with SLE. Disclosure of Interest: None declared